EDUCATIONAL ECOLOGY FOR STUDENT QUALITY DEVELOPMENT IN HIGHER EDUCATION INSTITUTE - Kumhom, Naitawan; นิรัญทวี, ศักดิ์ชัย; มีคุณ, โกศล; วัฒนาณรงค์, อัจฉรา (Thai Interdisciplinary and Sustainability Review, 2024)
Starting to study higher education is an important life change. How well students entering higher education can adapt to the changes and smoothly move through the transition from basic education to higher education institutions depends on their interaction with the context around them. Both in the family, the university, and society, which all have an influence on the development of student quality, including the growth of ideas, intelligence, and abilities. It arises from the development of three groups of educational ecological factors: students, student affairs, and educational institutions. This article aims to create understanding among teachers and personnel in higher education institutions and those involved in the relationship between students and the various contexts around them. It is called “educational ecology” using the theory of Bronfenbrenner as a framework for developing student quality. It is to help and support students to be able to cope with the changes that have occurred and achieve maximum prosperity, being complete human beings in the right direction according to the learning outcomes of bachelor's degree graduates in at least 4 areas, namely knowledge, skills, ethics, and personal characteristics according to the standards of higher education qualifications.